Determinants of the Decision to Provide Loans to Potential Investors on a Peer-to-Peer Lending Platform - Elsye Fatmawati; Parulian Parulian (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This research aim to reveal a number of possible factor influence investors decisions To do investment in Peer-to-peer (P2P) lending services in Indonesia. Study this use method survey with method distribute questionnaire through googleform to any of the users or a number of service banking . There are 82 questionnaires processed in research this using the PLS smart assistance program . Results in study this prove that Accumulation Transaction and Refund History , as well perception risk take effect to decision gift loan . With evaluate significant factor about party borrower , then potential investors will more easy for differentiate borrower one with others on P2P lending services With a number of factor , got is known that if party borrower could Fulfill all aspect such , then party borrower has give quality signal tall to potential investors. Results of research this expected could add nor expand knowledge knowledge as well as give proof new about a number of factor to be determinant decision gift loans on P2P lending services.